A Conceptual framework to analyse consequences of post conflict reconstruction interventions. (2018) - Sakalasuriya, Maheshika M.; Haigh, Richard P; Amaratunga, Dilanthi
Abstract: Reconstruction after war typically entails rebuilding soft and hard infrastructure. While an individual reconstruction intervention may focus on either or both these aspects, the overall reconstruction strategy takes a holistic approach and considers the integrated linkages among these interventions. From a policy perspective, it is important that a post conflict reconstruction (PCR) intervention should consider its potential positive and negative consequences while correctly positioning it within the whole PCR strategy. This study is an analysis of the potential consequences of a PCR intervention in the form of soft and hard infrastructure. Adopting a conceptual analytical method approach, it highlights the significance of accounting for consequences before a PCR intervention. In this study, a novel conceptual framework is proposed to analyse consequences of a PCR intervention, linking these consequences to context, intervention and long-term outcomes. The framework can be used as a basis to develop a policy framework to assess the consequences of reconstruction in a post conflict context.